TREATING PEOPLE WITH MENTAL DISORDER: Views from Islamic and Psychology and Sociology - Gustiani, Indah (Jurnal Moderasi, 2022)
Abstract Mental health disorders are conditions where individuals are unable to recognise and satisfy their needs. Mental health disorders are prevalent in society and have a major impact on individuals and communities. This article provides an overview of various mental health disorders in the community. It is a systematic review of books and e-journals published up to 2022 on related issues, the results of which are then analysed using the perspectives of Islamic psychology and sociology. This article shows that there is a misconception about how people with mental health disorders are treated in Indonesia. People with mental illness are perceived as dangerous, resulting in the avoidance and even isolation of sufferers. This article explains how to address this misperception through the help of Islamic psychology and sociology.   Keywords: Mental Health Disorders, Psychology, Islamic Sociology.